Social support in the workplace between teleworkers, office‐based colleagues and supervisors. (July 2016) - Collins, Alison M.; Hislop, Donald; Cartwright, Susan
Abstract : This paper draws upon the findings of qualitative interviews carried out with teleworkers, their office‐based colleagues and supervisory staff of a teleworking initiative introduced by a UK public sector local authority to explore workplace social support relationships. Our study found differences between office‐based and permanent teleworking staff in terms of social support. For teleworkers relationships at work are complex, with social support networks being established prior to working at home. By working from home, teleworkers were able to develop greater social support relationships with some colleagues, predominantly other teleworkers, while at the same time allowing them to distance themselves from negative work relationships. Overall, a social disconnection developed between teleworkers and office‐based staff. In contrast social support was more important for office‐based workers, who valued co‐worker relationships with other office‐based staff.